Evaluation of a Functional Single Nucleotide Polymorphism of the SARS-CoV-2 Receptor ACE2 That Is Potentially Involved in Long COVID - Luo, Yu-Si; Luo, Lei; Li, Wei; Chen, Yan; Wu, Guo-Feng; Chen, Fang; Shen, Hu-Yan; Li, Hong-Man; Guo, Ming-Yang; Yin, Sha; Zhang, Ke; Cheng, Zhong-Shan (Frontiers in Genetics, 2022)
Since the occurrence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Dec 2019, SARS-CoV-2 has led to a global coronavirus disease 2019 (COVID-19) pandemic. A better understanding of the human receptor ACE2 of SASR-CoV-2 at genetic level would help to combat with COVID-19, particularly for long COVID. We performed genetic analysis of ACE2 and searched for its common potential single nucleotide polymorphisms (SNPs) with minor allele frequency >0.05 in both European and Chinese populations that would contribute to ACE2 gene expression variation. We thought that the variation of ACE2 expression would be an important biological feature strongly affect COVID-19 symptoms, such as ‘brain fog’, which is highlighted by the fact that ACE2 acts as a major cellular receptor for SARS-CoV-2 attachment and is highly expressed in brain tissues. Based on the human GTEx gene expression database, we found rs2106809 exhibited a significant correlation with ACE2 expression among multiple brain and artery tissues. This expression correlation was replicated in an independent European brain eQTLs database, Braineac. The rs2106809*G also displays significantly higher frequency in Asia populations than in Europeans and displays protective effect (P=0.047) against COVID-19 hospitalization when comparing hospitalized COVID-19 cases with non-hospitalized COVID-19 or SASR-CoV-2 test negative samples with European ancestry from UK Biobank. Furthermore, we experimentally demonstrated that rs2106809*G could up-regulate the transcriptional activity of ACE2. Therefore, integrative analysis and functional experiment strongly support ACE2 SNP rs2106809 is a functional brain eQTL and its potential involvement in long COVID, which warrants for further investigation.